2003
DOI: 10.1097/01.tp.0000064210.92444.b5
|View full text |Cite
|
Sign up to set email alerts
|

CD103 mRNA levels in urinary cells predict acute rejection of renal allografts1

Abstract: CD103 mRNA levels in urinary cells are diagnostic of acute rejection of renal allografts. Because CD103 is a cell surface marker of intratubular CD8 CTLs, a noninvasive assessment of cellular traffic into the allograft may be feasible by the measurement of CD103 mRNA levels in urinary cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 19 publications
(19 reference statements)
2
77
0
1
Order By: Relevance
“…Regardless, these data document that an important component of the anti-graft response is not detectable by conventional immune monitoring approaches, which typically rely on sampling of peripheral blood. An alternative approach for detection of CD103 ϩ CD8 ϩ effectors is suggested by Ding et al (49), who have shown that CD103-expressing cells are detectable in the urine of renal transplant patients and that such levels correlate with rejection episodes. It now will be important to determine whether such assays possess the sensitivity and specificity to reliably predict tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, these data document that an important component of the anti-graft response is not detectable by conventional immune monitoring approaches, which typically rely on sampling of peripheral blood. An alternative approach for detection of CD103 ϩ CD8 ϩ effectors is suggested by Ding et al (49), who have shown that CD103-expressing cells are detectable in the urine of renal transplant patients and that such levels correlate with rejection episodes. It now will be important to determine whether such assays possess the sensitivity and specificity to reliably predict tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription to cDNA was performed by using TaqMan Reverse Transcription reagents (Applied Biosystems). Oligonucleotide primers and fluorogenic probes were designed and synthesized and tested for efficiency and validity for the measurement of mRNA levels of Suppressor of cytokine signaling1 (SOCS1), Suppressor of cytokine signaling2 (SOCS2), tissue necrosis factor ␣ (TNF␣), Complement 3 (C3), Ceruloplasmin (Cp), C-reactive protein (CRP), Guanylate nucleotide binding protein-1 (GBP1), interleukin-1␤ (IL-1␤), plasminogen activator inhibitor type-1 (PAI-1), Serum amyloid A-1 (SAA-), and transforming growth factor-␤ (TGF␤) (32). To measure mRNA levels of the internal control GAPDH transcript, a commercially available probe and primer mix (Applied Biosystems) were used.…”
Section: Rt-pcr Methodsmentioning
confidence: 99%
“…These observations include significantly increased levels of granzyme B and perforin, two cytotoxic effector molecules, in cells that were derived from rejection-associated urine compared with samples that were obtained in the absence of ACR, chronic allograft nephropathy, toxicity, or acute tubular necrosis (40). Other markers of the cytotoxic T cell pathway that are overexpressed in urine pellets during ACR episodes include the serine proteinase inhibitor-9 (PI-9), a natural antagonist of granzyme B (41), and CD103, expressed on alloreactive cytotoxic CD8 ϩ T cells (42). Along this theme, protein and transcript expression of the IFN-␥-inducible chemokine IP-10 and the chemokine receptor CXCR3 are elevated in the urine sediments of recipients with ACR (43), with variable predictive characteristics depending on the cutoff values used.…”
Section: What Can Urine Tell Us?mentioning
confidence: 99%